Anticonvulsive and antioxidant activity of aqueous root extract of Moringa oleifera in ferric chloride-induced epileptic rats - Koushik Ray,; Arkadeb Dutta,; Rimi Hazra,; Debjani Guha, (International Journal of Phytomedicine, 2012)
Moringa oleifera (MO), commonly known as drumstick tree in South Asian countries are consumed as food and have immense medicinal value. The consumption of the root of MO reduced neuronal hyper-excitability in psychiatric disorders. The present study has tested the efficacy of the aqueous root extract of MO in preventing epilepsy, a serious neurological disorder, from non-penetrating brain injury. Reducing power, polyphenol, flavonoid content of MO, and high performance liquid chromatographic identification of free radical scavenging compounds in the extract in the present study encourages its use for preventing free radical-induced epilepsy. Holtzman Strain adult rats, weighing 200-250 g, were assigned into four groups (n=6 in each group): normal control; sham operated; intracortically FeCl3 injected (100mM; 8micro litre); FeCl3 injected + MO pretreated (350mg/kg, orally) and FeCl3 injected + diazepam (DZ) pretreated (20mg/kg, i.p). Lipid peroxidation (LPO), catalase (CAT), superoxide dismutase (SOD) activities were studied as indirect parameters of free radical-induced brain damage. Serotonin, dopamine and nor-epinephrine were also evaluated biochemically from different brain regions. A statistically significant reduction in lipid peroxidation, CAT and SOD activity was observed in MO pretreated group when compared to the untreated epileptic rats. Serotonin level was found to be elevated significantly in cerebral cortex whereas dopamine and nor-epinephrine levels declined in the caudate nucleus and in cerebellum of MO-pretreated rats in comparison to untreated epileptic group and synchronizes with the changes with anticonvulsant diazepam. MO effectively prevents the advent of FeCl3 induced epilepsy by ameliorating free radical damage and by regulating protective neurotransmitters to restrain neuronal hyper excitability.